Proactive Marketing – Concept Development and Empirical Analysis - Väkeväinen, Virpi (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
In this thesis, proactive marketing is suggested to be a broader concept than existing research assumes. Although the concept has been mentioned in the context of competitive advantage in previous research, it has not been comprehensively described. This thesis shows that proactive marketing is more than investing in marketing communications of a company. Proactive marketing is described as a three-phased process that contains different customer value identification, creation, and delivery activities. The purpose of proactive marketing is essentially to anticipate and pursue market opportunities that bring value to the company’s stakeholders. Ultimately, proactive marketing aims at acting first on the market, shaping the markets, and thus reaching competitive advantage. The proactive marketing process is supported by the structures of an organization. Suitable structures for proactive marketing are identified in the thesis based on existing research and through an empirical analysis. Moreover, proactive marketing is related to two management theories: the dynamic capabilities framework and the empowerment of employees. A dynamic environment requires companies that pursue proactive marketing to change continuously. Dynamic capabilities are considered as tools of the management, which enable companies to create suitable conditions for the constant change. Empowerment of employees is a management practice that creates proactive behaviors in individuals. The empirical analysis is conducted in an online company operating in the rapidly changing marketplace of the Internet. Through the empirical analysis, the thesis identifies in practice how proactiveness manifests in the marketing process of a company, how organizational structures facilitate proactive marketing, and how proactive marketing is managed. The theoretical contribution of this thesis consist of defining the proactive marketing concept comprehensively and providing further research suggestions related to proactive marketing.